Analysis Of Identity Confusion And Mistaken Identities In The Comedy Of Errors - Ammar Muhammad Ra'id Zhafir Nur Haqiki Riyadi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This academic study explores the issue of identity uncertainty and mistaken identities in William Shakespeare's well-known farce,